The Influence of Restaurant Atmosphere on Customer Satisfaction in Sum Ting Wong Kitchen and Brew Bar - Adveni, Lusia Vreyda; Veronica You, Valleriant (Jurnal Manajemen Pelayanan Hotel, 2024)
This research aims to determine: The influence of restaurant atmosphere on customer satisfaction at Sum Ting Wong Kitchen and Brew Bar. This research is a descriptive analysis research using a quantitative approach. Data collection uses observation, documentation and questionnaires. The sample in this study was 35 respondents and used the random sampling method. The validity test used Cronbach's Alpha. Data analysis uses simple linear regression. The research results found that: restaurant atmosphere had a positive and significant effect on customer satisfaction, obtained a sig value. 0.000 <α 0.005 indicates that H1 is accepted. The simultaneous contribution or contribution of the restaurant atmosphere variable to customer satisfaction is 75.3% while 24.7% is determined by other variables not examined in this study. Keywords: Restaurant Atmosphere, Customer Satisfaction